DEVELOPING SIMPLE PROTOCOL ON NATURAL FEED CULTURE FOR REARING SEAHORSE JUVENILE - Henky Irawan; Tri Yulianto; Aidil Fadli Ilhamdy; Andre Jayardi (Program Studi Budidaya Perairan Universitas Maritim Raja Ali Haji, 2017)
Seahorse already cultured by two societies, where the problem was the lack of knowledge, skill, difficulty in finding the materials and tolls, also the problem in managing the seahorse juveniles rearing. The simple protocol with the steps that can easily understand for the non-expert society knowledge and the accessible for materials and tolls that affordable was the solution.